Tectonics of Enceladus' South Pole: Block Rotation of the Tiger Stripes. Issue 12 (21st December 2020) - Rossi, Costanza; Cianfarra, Paola; Salvini, Francesco; Bourgeois, Olivier; Tobie, Gabriel
Abstract: The South Polar Terrain (SPT) of Enceladus is a site with eruptions of gas and water ice particle plumes, which indicate internal geodynamic activity. These eruptions are located along a series of tectonic structures, that is, the Tiger Stripe Fractures (TSF), which are composed of regularly spaced, linear depressions. The SPT is surrounded by sinuous chains of ridges and troughs (the Marginal Zone). To unravel the tectonics that affect the region and its evolution, we performed specific structural mapping and quantitative analyses of brittle features from remotely sensed images. The results are consistent with a block rotation model, in which several tectonic regimes coexist. The TSF are left‐lateral strike‐slip faults that bound rigid elongated blocks. The blocks rotate clockwise and are enclosed in a regional scale right‐lateral kinematic framework expressed in the Marginal Zone. These two opposite and complementary kinematic regimes induce transtensional and transpressional regimes within the SPT. An evolutionary tectonic model is proposed for the past and future evolution of the SPT. This model confirms the role of tectonic‐related kinematics in icy satellites and contributes to preparations for future missions. Plain Language Summary: The South Pole of Enceladus is one of the most tectonically active regions in the outer solar system. It presents morphotectonic structures that play a key role in the investigation of the internal processes responsible for its crustal deformation and represent possible interaction with the subsurface ocean. In this contribution, we investigate the Enceladus South Polar Terrain (SPT) structures that are mainly represented by the Tiger Stripe Fractures. Their tectonic setting and kinematics are the object of the present study. The results obtained allow inference of block rotation tectonics induced by regional strike‐slip kinematics in the SPT. We propose an evolutionary tectonic model that presents past and future arrangements of the SPT. New findings have allowed identification of a significant compressional component within the study area, as well as the kinematics within this terrain. Key Points: Tectonic activity at Enceladus' south pole is consistent with clockwise block rotation tectonics Regional right‐lateral strike‐slip kinematics induces transtensional and transpressional regimes in the south polar region An evolutionary tectonic model is proposed for the past, present and future settings of Enceladus' south polar structures